Physical parameters and performance values in starters and non-starters volleyball players: A brief research note - M.C. Marques; D.A. Marinho (Desafio Singular, 2009)
The aim of this paper was to investigate the anthropometric and strength characteristics of elite male volleyball athletes and determines if differences exist in these characteristics between starters (S) and non-starters players (NS). A group of 22 professional male team volleyball players participated in the study and the players were categorized as S (n= 13) and NS (n= 9). Anthropometric characteristics, countermovement jump, overhead medicine ball throwing and maximal dynamic strength were evaluated in all the subjects. Significant diferences in age, hight and weight were noticed between S and NS. There were no significant differences between the two groups in strength and power values, except for squat performance, where S were significant strong than NS. These findings provide normative data for elite male volleyball players competing in specific playing status. From a practical perspective, sport scientists and conditioning professionals should take specicif lower body strength characteristics of volleyball players into account when designing individualized training stauts specific training programmes.